The Mediating Role of Perceived Organizational Support in the Relationship Between High Performance Work System and Employee Well- Being at XYZ Hospital, South Jakarta - Arischa Audiana (Budapest International Research and Critics University, 2022)
The aim of this study was to see whether or not perceived organizational support had a role in moderating the relationship between high performance work systems and employee well-being at XYZ Hospital in South Jakarta. A quantitative approach was used, using a saturated sample of 72 persons. The data is processed using descriptive data analysis techniques with partial least squares - structural equation modeling (PLS-SEM), yielding the following results: high performance work system has a positive effect on employee well-being, perceived organizational support has a positive and effect on employee well-being, and high-performance work system has a positive effect on perceived organizational support. In addition, high performance work system has a positive effect on employee well-being through perceived organizational support